Increasing the required slip range of wound induction generator in wind power systems - Ali Dalabeeh; Al-Mofleh Anwar; Tariq M. Younes; Ayman Al-Rawashdeh; Ayman Hindi (Institute of Advanced Engineering and Science, 2020)
Eddy currents losses in the rotor in high power generators do not allow operators, under high values of slip, to regulate voltage and control of reactive power flow. The paper presents a method that can accurately estimate the eddy current losses in electric machines with a less complicated procedure. The suggested method allows researchers to analyze and reduce the losses, and consequently, to improve the wind turbine induction generators efficiencies. The given approach, based on the conventional electric machine theory and the parameters supplied by the manufacturers, predicts the eddy current losses theoretically without the need of the measured material loss data or BH curve. Increasing the range of slip variation of induction motor can be achieved by using a rotor of two layers in the radial direction with different parameters. The first layer is a laminated layer of height (h), and the second is a solid (the rotor yoke). The computation of eddy current losses is useful to change the design of the machine to minimize the losses. This paper presents a detailed modeling of the effect parameters on the eddy current losses in wind turbine induction generator.